2018
DOI: 10.1002/rcs.1912
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted total hip arthroplasty: Clinical outcomes and complication rate

Abstract: Robotic-arm-assisted THA demonstrates favourable short-term outcomes and does not result in a higher complication rate compared to non-robotic THA as reported by the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 39 publications
0
43
0
1
Order By: Relevance
“…Robotic arm assisted devices have been shown to have several intraoperative advantages related to outcomes, as well as provide excellent postoperative satisfaction. 18,19…”
Section: Discussionmentioning
confidence: 99%
“…Robotic arm assisted devices have been shown to have several intraoperative advantages related to outcomes, as well as provide excellent postoperative satisfaction. 18,19…”
Section: Discussionmentioning
confidence: 99%
“…Angeles activity level in Mako THA than those for manual THA, at a minimum of one-year follow-up [20]. Perets et al followed 162 patients undergoing rTHA and reported reduced pain, increased patient satisfaction, and improved functional outcomes as assessed using HHS and Forgotten Joint Score at a minimum two years follow-up [21]. To our knowledge, the present study is one of few to compare outcomes between rTHA and nTHA.…”
Section: Discussionmentioning
confidence: 90%
“…The radiographic inclination and anteversion angles in the rTHA group were 42.2 ± 2.2 (range 38-47) and 20.3 ± 1.6 (range, [16][17][18][19][20][21][22][23][24], respectively, whereas those in the nTHA group were 40.5 ± 4.5 (range, 32-44) and 19.9 ± 3.6 (range, 14-33), respectively. No statistically signi cant difference was observed between the groups.…”
Section: Resultsmentioning
confidence: 99%
“…Robotic‐arm assisted technology has been shown to recreate the head center, offset and leg length more accurately when compared to manual technique. In a few published studies, robotic THA has been associated with improved patient reported outcomes, decreased dislocation rates, and high forgotten joint scores. However, these data have been on cohorts of patients with primary osteoarthritis of the hip.…”
Section: Introductionmentioning
confidence: 99%